Studi Motivasi Guru PJOK dalam Menjalankan Pembelajaran Jasmani di Kecamatan Kalikotes Klaten - Nugroho, Hanif; Dimyati, Dimyati; Wibowo, Yuyun Ari (Jurnal Porkes, 2025)
This study aims to identify factors that influence the motivation of physical education, sport and health teachers in carrying out learning in Kalikotes Sub-district, Klaten District. Using a descriptive quantitative approach, this study involved 12 PJOK teachers as respondents. Data were obtained through questionnaires that included intrinsic factors, such as enjoyment of teaching, as well as extrinsic factors, such as rewards, work environment, school support, students, and peers. Data collection was carried out using an instrument in the form of a questionnaire. The results showed that the level of motivation of PJOK teachers was classified as very high, with an achievement of 88.26%. Analysis of pleasure 88.75%, analysis of reward aspects 87.92%, analysis of environmental aspects 85%, analysis of school aspects 87.50%, analysis of student aspects 91.25%, analysis of friend aspects 88.26%. This motivation is formed through a combination of internal drive and external support. A sense of enthusiasm in teaching is the main factor from within the teacher, while a supportive work atmosphere, appreciation, and positive social relationships are external reinforcers. In conclusion, the high motivation of PJOK teachers is the result of the cooperation of various factors that support each other.